Folklor lisan â€œDendang Malam Bimbang Gedang Tepuk Tariâ€ dalam adat perkawinan kota Bengkulu - Eli Diana; Dhanu Ario Putra (Universitas Ahmad Dahlan, 2019)
Dendang is one of the oral folklores of Bengkulu city. This study aims to describe dendang Tepuk Tari in the marriage customs of Bengkulu city, the form, function, and values. The method used in this research is descriptive qualitative method using recording techniques, interviews, listening, and taking notes and the Snowball sampling technique. The main data in this study are the chanting poems taken from the video footage that was sung and equipped with the results of interviews with several informants. The results of this study indicate that the dendang is not only in the form of traditional songs and music, but is collaborated with seven traditional dances that resemble the movements in pencak silat. The poetry used consists of: 1) regular rhymes, and 2) talibun that are performed by means of reciprocating between the players using Bengkulu language and describing the lives of Bengkulu people. From the results of data analysis (poetry), this dendang functions as; 1) means of entertainment, 2) forms of community identity, 3) social criticism, and 4) means of educating and having values: 1) philosophical, 2) religious, and 3) sociological.